Formulasi Rumah Sakit Puri Mandiri Kedoya Melalui Pendekatan Analisis Swot Untuk Menghadapi Diberlakukannya Bpjs Kesehatan - Nuria Cipta Sari dan Anas Lutfi (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The purpose of this paper is to analyze the external and internal conditions of the Hospital that can help Puri Mandiri Kedoya Hospital in preparing its strategy plan to face BPJS Health and can provide an overview in developing a comprehensive strategy for Puri Mandiri Kedoya Hospital in making adjustments to the system BPJS Health. The method of writing this work includes the discussion of supporting theories as well as taking necessary data through complementary books, text book or other sources related to this scientific paper. The authors includes data sources from BPJS health book pocket and all related data which has been published, thus the data used is accurate and issue by the government. The results of this study were taken from the analysis of this study were taken from the analysis of both the internal analysis and external analysis of hospitals, by combining the strengths and threats of independent self-sufficiency Puri Mandiri Kedoya Hospital by selecting efficient suppliers for inventory, collaborating with management and medical staff on the use of medicines and health care tools, time-efficient services with the use of integrated medical documentation with computerized systems. Establish partial referral cooperation between surrounding hospitals. Efficiency of Hospital tariff system in preparing cross-subsidy counting to prevent net loss by joining independent Puri mandiri Kedoya Hospital with government program through BPJS Health to be able to survive in service process.